I-V curve tracer based on capasitor charging method for photovoltaic (PV) power system
Measuring the I–V characteristics is of high importance since it can be considered as a quality and performance certificate for each PV generator. The capacitor charging method is considered as the cheapest and most precise measuring methods for PV generators. The equivalent circuit of the PV generator is utilised with a capacitor serving as the load and then a transient analysis is performed on the circuit to obtain the charging voltage and current of the capacitor as a function of time. This method can also be used to obtain their differentials as a function of the capacitor size and the short-circuit current. This method was proposed as a solution to the low-speed I-V curve tracing problem in the resistor method. It was also suggested as a solution to the power sinking issues that are often associated with DC-DC converters. In order to achieve a fast, smooth and accurate curve information, the capacitor size is considered the main concern in this proposed method. The utilized equations help to calculate the proper capacitance size to measure the I-V characteristics. It also takes into consideration the speed acquisition of the measuring system as illustrated using the measurement samples given in this study for the I-V curve with acceptable accuracy. The capacitor size is directly proportional to the short-circuit current and indirectly proportional to the PV generator’s open circuit voltage. The capacitor charging durations that will represent the I-V characteristics curve will be simulated through a computerised simulation using the MATLAB software. The results of this thesis shows that the tracing durations for both performed conditions of UTC and PSTC was less than one second in order to fully trace and graph the I-V curve.